DISTRIBUSI IKAN DEMERSAL Dl PERAIRAN PANTAI TELUK SEMARANG - SUHARIYONO SUHARIYONO (JURNAL LITBANG PROVINSI JAWA TENGAH, 2005)
Familly Ariidae is a potential and important resource, but information on the distribution and quantity of Demersal fish are relatively scarce and limited, especially those at Semarang Gulf Water. Since is no initial data concerning the existence offamily Ariidae resources. The method for data collection of this research was survey, with samples collected from Korowelang ( Location I), Semarang ( Location II), and Morodemak ( Location Ill). Each location consists of 5 depths, about ± 1m, ±5m, ± 1Om, : ±15m, and> 20m Sampling parameter using Push Net in the depth about ±l m, and Beam Trawl in the depth of± 5m, ± 1Om, ± 15m, and > 20m. The Size Beam is 2 x 0,6 m, and Mesh Size of body and cod end each of 2,5m and 0,5 cm. Respectively, the abundance was analized using Swept area Method. Total Dernersal fish found during the research was 6.561 Ind, the most abudance( Ind/ 100 m ) was from ± 1 5m. The Distribution of Demersal fish tends to take place randomly, and bigger variety found on most species. The biggest quantity was found at about ± 15m below surface, while the smallest species and quantity were found at about ± 11 m and >20m below surface